Molecular systematics of Malagasy poison frogs in the Mantella betsileo and M. laevigata species groups - Rabemananjara, Falitiana C.e.; Crottini, Angelica; Chiari, Ylenia; Andreone, Franco; Glaw, Frank; Duguet, Remí; Bora, Parfait; Ramilijaona, Olga Ravoahangimalala; Vences, Miguel (Zootaxa, 2007)
Malagasy poison frogs of the genus Mantella with its 16 species are currently sub-divided into 5 major groups. Of these, the Mantella betsileo group is traditionally understood as containing four species, Mantella betsileo, M. expectata, M. viridis and M. manery, while the M. laevigata group is considered to be monospecific. A phylogenetic analysis of samples from multiple localities of all species in these two groups, based on sequences of the mitochondrial cytochrome b gene, shows the existence of several well-distinct clades in what is currently considered to be Mantella betsileo: (1) central-western populations from Kirindy, Isalo, and near Antsirabe close to the Betsileo region, to which the name M. betsileo is to be applied, (2) populations of the north-east and north-west, which are closely related to M. viridis and to which the name M. ebenaui is to be applied, and (3) a clade from southernmost Madagascar and from the Tsingy de Bemaraha, which is sister to M. expectata and furthermore includes important intra-clade variation, therefore probably representing one or two undescribed species. Our data also support a large genetic distance of M. manery to all other species and its probable sister-group relationship to the sympatric M. laevigata; M. manery is consequently transferred from the M. betsileo group to the M. laevigata group.